Closed‐loop subspace identification methods: an overview. Issue 10 (1st July 2013) - van der Veen, Gijs; van Wingerden, Jan‐Willem; Bergamasco, Marco; Lovera, Marco; Verhaegen, Michel
Abstract : In this study, the authors present an overview of closed‐loop subspace identification methods found in the recent literature. Since a significant number of algorithms has appeared over the last decade, the authors highlight some of the key algorithms that can be shown to have a common origin in autoregressive modelling. Many of the algorithms found in the literature are variants on the algorithms that are discussed here. In this study, the aim is to give a clear overview of some of the more successful methods presented throughout the last decade. Furthermore, the authors retrace these methods to a common origin and show how they differ. The methods are compared both on the basis of simulation examples and real data. Although the main focus in the literature has been on the identification of discrete‐time models, identification of continuous‐time models is also of practical interest. Hence, the authors also provide an overview of the continuous‐time formulation of the identification framework.